2016
DOI: 10.1007/s00784-016-1867-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of periodontal ligament and gingiva-derived mesenchymal stem cells for regenerative therapies

Abstract: Gingiva-derived MSCs may represent an accessible source of messenchymal stem cells to be used in future periodontal regenerative therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 46 publications
0
26
0
Order By: Relevance
“…Human GMSCs are homogenous, not tumorigenic [97], and easy to be isolated [98] and display stable phenotype. The most significant advantage of human GMSCs is without any ethical problems in clinical application [99].…”
Section: Mscs Derived From Other Tissuesmentioning
confidence: 99%
“…Human GMSCs are homogenous, not tumorigenic [97], and easy to be isolated [98] and display stable phenotype. The most significant advantage of human GMSCs is without any ethical problems in clinical application [99].…”
Section: Mscs Derived From Other Tissuesmentioning
confidence: 99%
“…Gingival fibroblasts were found to express variable levels of mRNA for alkaline phosphate and bone morphogenetic protein 2/4 (BMP2/4) in vitro, which demonstrated that appropriate stimuli may direct their capacity of hard tissue formation [8]. By the same token, gingival mesenchymal stem/progenitor cells (GMSCs), with self-renewal capabilities, remarkable differentiation potential, long-term telomerase expression, and outstanding immunomodulatory properties have been isolated [9,10]. GMCSs preconditioned in an osteogenic differentiation medium demonstrated on the mRNA level expression of bone specific markers, including Runx2, collagen I, collagen III, ALP, osteonectin (ON), osteopontin (OP), osteocalcin (OC), and osterix [9].…”
Section: Introductionmentioning
confidence: 99%
“…GMCSs preconditioned in an osteogenic differentiation medium demonstrated on the mRNA level expression of bone specific markers, including Runx2, collagen I, collagen III, ALP, osteonectin (ON), osteopontin (OP), osteocalcin (OC), and osterix [9]. GMSCs showed few inflammation-related changes when incubated with proinflammatory mediators (TNF-α, IL-1β), which suggested good response to unfavorable environmental conditions [10]. A bone regenerative capacity of GMSCs has been confirmed by multiple studies, as these cells were able to repair the critical size mandibular/calvarial defects in animals [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…These results agree with other studies devoted to gingival MMSC that reported similar phenotype characteristics, differentiation potential and stable genomic behavior. 19,39,40 Also, we determined high proliferative capacity of AMC which remained constant from primary to long-term cultures. It should be noted that the population doubling time for bone marrowderived MMSC reaches only 55 § 3 hours under similar cultivation conditions.…”
Section: Discussionmentioning
confidence: 99%
“…10 It was described earlier that MMSC derived from different tissues can possess various colony-forming unit and differentiation efficiency as well as different proliferative capacity. 19,20,21 Another important issue is availability of the source tissue, namely invasiveness of manipulation and risk of complications, related to sample procurement. 22 Gingival mucosa is one of promising sources of MMSC due to availability and minimally invasiveness of its procurement and ability of gingival mucosa wounds to heal without formation of scar.…”
Section: Introductionmentioning
confidence: 99%